Mucoadhesive Polymer Hyaluronan as Biodegradable Cationic/Zwitterionic-Drug Delivery Vehicle - Francisco Torrens; Gloria Castellano (International Association of Physical Chemists (IAPC), 2015)
Mucoadhesive polymers in pharmaceutical formulations release drugs in mucosal areas. They interact and fix to mucus via molecular interpenetration, etc., which increase drug bioavailability. Polymers physicochemical properties affect formulation mucoadhesion, rheological behaviour and drug absorption. Hyaluronan (HA) is selected as a mucoadhesive and biodegradable polymer. Geometric, topological and fractal analyses are carried out with program TOPO. Reference calculations are performed with algorithm GEPOL. Procedure TOPO underestimates molecular volume by 0.7%. Error results 5% in surface area and derived topological indices. Solvent-accessible surface is undercalculated by 3%: from hexamer HA to HA·3Ca and hydrate, the hydrophobic term rises by 42% and decays by 26%, and hydrophilic part drops by 14% and rises by 58% in agreement with the number of H-bonds. Accessibility rises by 9% and decays by 8%. Fractal dimension is underevaluated by 1% and for HA it results 1.566; on going to HA·3Ca and hydrate it rises by 2% and 1%. External-atoms dimension increases by 11%: for HA it results 1.725. When going to HA·3Ca and hydrate, it augments by 4% and 0.3%. On going from HA to HA·3Ca and hydrate, nonburied minus molecular dimension enlarges by 20% and decays by 9%. The hydrate globularity is lower than for water, Ca2+ and averages of O-atoms in HA. Ca2+ rugosity is smaller than for hydrate, averages of O-atoms in HA and water. Ca2+ and water accessibilities are greater than for hydrate. As cations exchange in HA·3Ca requires Ca2+ alteration, rises of drug zwitterionic character and acidic pH increase absorption.